The Effect of Drinking Water Temperature and Stocking Density on Broiler Performance, Meat Quality and Some Behavioral Traits at High Ambient Temperature - Kaya, M; Dereli Fidan, E (Journal of the Hellenic Veterinary Medical Society, 2023)
The present study examined the effect of drinking water temperature and stocking density on performance (cumulative body weight gain, feed intake, and feed conversion ratio), meat quality, and behaviour traits (eating, drinking, lying, standing, and dust bathing) in broilers. A total of 360 broiler chicks (Ross 308) were randomly divided into 6 experimental groups, in a 2x3 factorial arrangement of drinking water temperature (10°C or 31°C), with stocking density (12, 15 or 18 birds/m2), each consisting of 4 replicate pens. Meat quality traits (pH15, L*, CL, and WHC), lying and standing behaviours were affected by water temperature. The stocking density significantly affected the cumulative body weight gain, feed intake, feed conversion ratio, color of breast meat [lightness (L*), redness (a*), yellowness (b*)] of broiler chickens. In conclusion, management practices such as stocking density and drinking water temperature in broilers could reduce the detrimental effects of high ambient temperature on growth performance, meat quality traits, and behaviour.